Development of TaqMan® MGB fluorescent real-time PCR assay for the detection of anatid herpesvirus 1 - Shen Chanjuan; Wang Mingshu; Cheng Anchun; Guo Yufei; Jia Renyong; Chen Shun; Zhang Na (Virology Journal, 2009)
Abstract Background Anatid herpesvirus 1 (AHV-1) is an alphaherpesvirus associated with latent infection and mortality in ducks and geese and is currently affecting the world-wide waterfowl production severely. Here we describe a fluorescent quantitative real-time PCR (FQ-PCR) method developed for fast measurement of AHV-1 DNA based on TaqMan MGB technology. Results The detection limit of the assay was 1 × 101 standard DNA copies, with a sensitivity of 2 logs higher than that of the conventional gel-based PCR assay targeting the same gene. The real-time PCR was reproducible, as shown by satisfactory low intra-assay and inter-assay coefficients of variation. Conclusion The high sensitivity, specificity, simplicity and reproducibility of the AHV-1 fluorogenic PCR assay, combined with its wide dynamic range and high throughput, make this method suitable for a broad spectrum of AHV-1 etiologically related application.